Proof of concept and feasibility studies examining the influence of combination ribose, adenine and allopurinol treatment on stroke outcome in the rat. (28th June 2017) - Faller, Kiterie M.E.; Leach, Joshua; Johnston, Pamela; Holmes, William M.; Macrae, I. Mhairi; Frenguelli, Bruno G.
Background: Cerebral ischaemia results in a rapid and profound depletion of adenosine triphosphate (ATP), the energy currency of the cell. This depletion leads to disruption of cellular homeostasis and cell death. Early replenishment of ATP levels might therefore have a neuroprotective effect in the injured brain. We have previously shown that the ATP precursors, D-ribose and adenine (RibAde), restored the reduced ATP levels in rat brain slices to values similar to those measured in the intact rodent brain. The aim of this study was to assess whether RibAde, either alone or in combination with the xanthine oxidase inhibitor allopurinol (RibAdeAll; to further increase the availability of ATP precursors), could improve outcome in an in vivo rodent model of transient cerebral ischaemia. Methods: After 60 min occlusion of the middle cerebral artery, and upon reperfusion, rats were administered saline, RibAde, or RibAdeAll for 6 h. Baseline lesion volume was determined by diffusion-weighted MRI prior to reperfusion and final infarct volume determined by T2-weighted MRI at Day 7. Neurological function was assessed at Days 1, 3 and 7. Results: Ischaemic lesion volume decreased between Days 1 and 7: a 50% reduction was observed for the RibAdeAll group, 38% for the RibAde group and 18% in the animals that received saline. Reductions in lesion size in treatment groups were accompanied by a trend for faster functional recovery. Conclusion: These data support the potential use of ribose, adenine and allopurinol in the treatment of cerebral ischaemic injury, especially since all compounds have been used in man.